(untitled) (Altre Modernità, 2021)
Wall/Walls Shapes and representations of the wall in languages, literatures, and visual arts (edited by) Alessandra Goggio, Peggy Katelhön and Moira Paleari TEXTS BY: A. Adverse, M.D. Alonso Rey, C. Balma-Tivola, L. Cazzato, M.R. Consolaro, M. Demata, I.H. Fierbințeanu, C. Fossaluzza, J. Gunia, L. Jusufi, G. Mangiapane, E. Marino, A. Mozolevska, N. Palliwoda, P. Panizzo, O. Polishchuk, V. Sauer, S. Sauermilch, C. Storskog, S. Verdiani Cover: Méndez Blake, Jorge, Amerika, 2019. The editors would like to thank Jorge Méndez Blake for granting the permission to publish one of his works as the cover of AM #25.